(untitled) (Actualizaciones en Sida e Infectología, 2023)
On March 12, Dr. Jorge Alberto Corral passed away in the city of Mar del Plata. The ASEI Editorial Secretariat asked me to remember him in a brief review. It is a very difficult task to write about a colleague whose loss is so recent, and with whom we shared a life of work in our beloved Hospital Interzonal General de Agudos Oscar Alende of Mar del Plata, but I will try. We started working with Jorge in 1981. He had already been working for some years as an assistant physician in the Clinical Medicine Service and I was returning to the hospital with an appointment in the same service. We were in charge of a six-bed ward and, right from the start, we had several things in common: a passion for hospital medicine, a desire to grow and a love for residency. He was proud of his record as Chief Resident of Clinical Medicine at the Hospital de Clínicas of Buenos Aires, and I was proud of my record as Chief Resident at the Hospital Oscar Alende. We shared this privilege, we were both very good readers and loved teamwork. At that time, as always, infectious pathologies were prevalent in the hospital, and the management of antibiotics was a serious problem. It was then that what was to become the starting point of a great project came about, when he said to me, over coffee in the basement bar: “Are you up for us to standardize the use of antibiotics for the main infections we see in the hospital?”. So we did it, and that was the beginning of infectiology in the hospital and in our city. Then followed the fine- tuning of bacteriology, the adequacy of resources, the organization of the office and interconsultations, infection control and so on... Everything to be done, surely ways known to most of you. Jorge managed, not without effort, to have the hospital’s organization chart incorporate the Infectious Diseases Unit, which later became a ward, and of which he was the head until his retirement. Clinical infectious disease practice was in its infancy and we drew on the experience of our colleagues in Buenos Aires, who were more advanced in the process. Jorge would establish the contacts and they would come to the hospital to offer us their knowledge in the management of an infectious disease service. I remember in those early days Dr. Daniel Stambouliam, Dr. Liliana Clara, Dr. Abel Jasovich and Dr. Horacio López, among others. When they came, we used to organize athenaeums, discuss case reports and update topics of the specialty. Attending were clinicians, Clinical Medicine residents and colleagues from other health institutions in the area. It was a period of significant growth, which led to the incorporation of new professionals to the service, led by an active, inspiring and respected chief as was Jorge Corral throughout his career. I cannot fail to mention what AIDS meant for the Infectious Diseases Ward and for the entire hospital. Under Jorge’s coordination and with the involvement of Dr. Alejandro Ferro, we had to organize the care, hospitalization and follow-up in a context of initial uncertainty, the difficulty of medical, social and institutional management in the midst of an explosion of cases that occurred in that period in Mar del Plata, and whose only place of care was the Infectious Diseases Department. The chief was able to handle this situation successfully, solving problems and gaining an excellent experience for himself and for all of us, which made the service a true benchmark in the field. In 1998, he promoted the creation of the Infectious Diseases Residency, from which 22 residents and 2 attending physicians who obtained the Specialty have graduated to date, and who have been populating public and private health institutions in the city and other parts of the country, representing their place of training with prestige. Clinical research was a widely achieved goal. Dr. Corral led our group, which joined the best research centers, conducting a wide variety of major clinical trials. His work in health care also gave way to university teaching and he was the head of the Infectious Diseases and Microbiology Department at the School of Medicine of the FASTA University of Mar del Plata. He was also a member of the Argentine Society of Infectious Diseases and the Infectious Diseases Society of Mar del Plata, with active participation in the congresses and conferences of both scientific societies. Great person and excellent professional, father of Mar del Plata’s infectious diseases practice, referent of local and national infectology, trainer of generations of clinicians and infectologists. We will all miss you, Jorge “Nono” Corral.